Creating Collaborative Advantages Through Coordination of Regional Development Activities - Marijana Sumpor (European Regional Science Association (ERSA), 2006)
Through the increasing importance of networking and use of participatory strategic planning approaches in the regional development practice, it seems that local and regional development theory moves from the concept of competitive advantages towards collaborative advantages. This conceptual move implies a redefinition of inter- and intra-institutional relations of the public and private sector, and therefore, calls for defining new forms of governance. The exploration of the concept of collaborative advantages might contribute to a better understanding of the relations between the European concepts of competition and cohesion. As networking in various forms and creation of collaborative advantages requires significant "coordination" of multiple development actors and activities across different territorial levels, a broad spectrum of research questions can be opened. This research paper is focussed on the problem of coordination, which is often mentioned as one of the main problems of local and regional development. Before any development activity can be coordinated, some preconditions have to be fulfilled, namely development actors have to be willing to communicate and to cooperate. Only then collaboration in the implementation of concrete development activities might occur. This process involves formal and informal institutional relationships, as well as multi-level governance. The main goal of this research paper is to explain and define the concept of collaborative advantages and coordination in the context of regional development policy. In Addition, a conceptual policy coordination model that combines horizontal and vertical relationships between the main development actors, while planning and implementing local and regional development activities, is presented. The regional development policy coordination model is developed on the basis of recent insights into regional, institutional, organizational and planning theories and practice. It is tested on the basis of the institutional framework and strategic planning experiences in Croatia, particularly in the context of the future integration into the European Union. The results indicate that the model is applicable in other countries and it contributes to a better understanding of institutional relationships in coordinating regional development activities and creating collaborative advantages.
Keywords: 330